УЛЫЎМА БИЛИМ БЕРИЎ МЕКТЕПЛЕРИНИҢ МАТЕМАТИКА ПӘНИ САБАҚЛЫҚЛАРЫНДАҒЫ АЙЫРЫМ МАТЕМАТИКАЛЫҚ ТЕРМИНЛЕР ТУЎРАЛЫ ПИКИРЛЕР - Курбанбаев, Т.К.; Нуржанов, Б.О. (SCIENCE and SOCIETY, 2024)
The article provides opinions on some mathematical terms in school textbooks on mathematics.
Keywords: term; terminology; school textbooks on mathematics